2018
DOI: 10.1111/eci.13041
|View full text |Cite
|
Sign up to set email alerts
|

ADMA and NT pro‐BNP are associated with overall mortality in elderly

Abstract: Background Increased asymmetrical dimethylarginine ( ADMA ) and NT pro‐ BNP concentrations have been associated with mortality in patients with cardiovascular ( CV ) disease and the general population. The use of these prognostic markers in an older population is not established yet. The aim of the present study was to investigate the prognostic value of age, sex, BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…Second, the same groups of drugs did not have the same effect regarding lowering plasma NT-proBNP concentration. Third, in contrast to previously published studies [15,18,19], we did not confirm a positive correlation of plasma ADMA concentration with NT-proBNP or the prevalence and severity of LVDD, HF, NYHA class, or CV risk, probably due to the previously mentioned drug influence. Fourth, similarly to other studies, we also confirmed that there is a positive correlation between the prevalence and severity of LVDD, CV risk factors, CVDs [5][6][7], estimated CV risk [36], NT-proBNP concentration [37], and HF [38,39].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Second, the same groups of drugs did not have the same effect regarding lowering plasma NT-proBNP concentration. Third, in contrast to previously published studies [15,18,19], we did not confirm a positive correlation of plasma ADMA concentration with NT-proBNP or the prevalence and severity of LVDD, HF, NYHA class, or CV risk, probably due to the previously mentioned drug influence. Fourth, similarly to other studies, we also confirmed that there is a positive correlation between the prevalence and severity of LVDD, CV risk factors, CVDs [5][6][7], estimated CV risk [36], NT-proBNP concentration [37], and HF [38,39].…”
Section: Discussioncontrasting
confidence: 99%
“…All CV risk factors known so far, as well as CVDs, increase the concentration of ADMA in such a way that they lead to the excessive formation or inhibition of its degradation [17]. We found in the literature that ADMA showed a positive correlation with the incidence of LVDD [18] and N-terminal pro-brain NP (NT-proBNP) values [19], and, similarly to NT-proBNP, can further improve the stratification of the risk of cardiac decompensation, major adverse CV events, and mortality in patients with HF [20,21]. Through our research, we aimed to determine whether we could contribute to a personalized understanding of the (residual) CV risk assessed via the SCORE2 algorithm by measuring the plasma concentration of the biomarkers ADMA and NT-proBNP with dependence on LVDD.…”
Section: Introductionmentioning
confidence: 95%
“…Particular attention should be paid to the role of the assessment of natriuretic peptides in older patients hospitalized due to exacerbation of HF. It is known that NT-proBNP predicts mortality among the older and very elderly patients with chronic HF [33]. In the elderly population with HF, the higher cut-off value for NT-proB-NP should be considered.…”
Section: The Specific Characteristics Of the Elderly Populationmentioning
confidence: 99%
“…Compared to Hcy, significant associations of ADMA with mortality are limited to subjects with end-stage renal disease [11] , angiographic coronary artery disease (CAD) [12] , acute myocardial infarction [13] , after percutaneous coronary intervention [14] , and patients aged over 65 years old [15] . Two cohort studies [ 16 , 17 ] maru, a cohort of the Seven Countries Study [19] ).…”
Section: Introductionmentioning
confidence: 99%